Archetypical Signs of the Kolomyika in the Ukrainian Music of the 21st Century - Maryna VARAKUTA; Daryna KUPINA; Maryna VOTINTSEVA (Studia Universitatis Babeş-Bolyai. Musica)
The article is devoted to studying the implementation/manifestation/reflection of archetypal features of kolomyika, as a traditional genre of Ukrainian folk art, in the music of Ukrainian composers. The kolomyika has been determined to be a typified intoneme, a semantic-meaning unit, with a set of specific speech features, which sprouts/appears in the music of Ukrainian composers, connecting with concert genres. It has been revealed that the kolomyika intonation complex often serves as the basis of an instrumental piece, which has been confirmed by a large number of Ukrainian composers’ opuses, since the second half of the 19th century to the present day. Examples of the kolomyika genre usage have been proven to be sporadic in choral music. That is why Kolomyika for mixed choir, percussion instruments, and piano by the Ukrainian composer Volodymyr Zubytsky is an interesting example of the embodiment of the genre within the framework of choral music. It is proved that the genre of kolomyika is interpreted by Zubytsky as a universal intonation-semantic model, raised to the level of philosophical generalization, which allows the composer to address the exciting socio-political issues of the present employing an artificial genre.